The impact of game reward mechanisms on enhancing elementary school students’ English vocabulary acquisition based on the ARCS motivation model - Yang, Ching-Yu; Chang, Rong-Chi; Hsieh, Sheng-Min (International Journal of Educational Technology and Learning, 2025)
As globalization progresses, the need for proficiency in a common language grows, placing emphasis on effective language learning. Vocabulary retention, as a core aspect for students’ language learning, remains challenging for non-native learners. To achieve this, many educational institutions incorporate digital technologies that support long-term memory retention. Game-based learning, especially when integrated with reward mechanisms, has been shown to enhance students’ motivation by providing goal-oriented incentives. This study developed the "Max Vocab Fun" app, an English vocabulary learning tool for third-grade elementary students, incorporating game-based rewards. A one group, pre-test and post-test quasi-experimental design examined the app’s impact on students’ vocabulary acquisition and motivation. The ARCS Model Learning Motivation Scale used to measure the motivational impact of the app’s reward mechanisms. Findings show significant improvement in vocabulary retention, with the gamified approach notably benefiting lower-achieving students. Overall, the app effectively increased motivation and contributed to a more positive learning environment, demonstrating the potential of integrating game-based rewards into language learning to improve outcomes for diverse student groups.